2004
DOI: 10.2223/1204
|View full text |Cite
|
Sign up to set email alerts
|

Leptin as a marker of sexual dimorphism in newborn infants

Abstract: Fonte financiadora: Fundação de Amparo à Pesquisa do Estado de São Paulo -FAPESP.Artigo submetido em 17.12.03, aceito em 26.04.04. AbstractObjective: To determine cord blood leptin levels in newborns appropriate for gestational age, according to gender, birth weight, birth height and ponderal index.Methods: A cross-sectional study was carried out with 132 term newborns appropriate for gestational age (68 females, 64 males), gestational age between 35-42 weeks. Data were collected through interviews with the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…These observations are compatible with findings that infants with congenital leptin deficiency or leptin receptor gene mutation have normal birth weights (15,16). On the contrary, cord leptin concentration explained up to 15% of the variance in infants' skinfold AGA -appropriate for gestational age; SGA -small for gestational age.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These observations are compatible with findings that infants with congenital leptin deficiency or leptin receptor gene mutation have normal birth weights (15,16). On the contrary, cord leptin concentration explained up to 15% of the variance in infants' skinfold AGA -appropriate for gestational age; SGA -small for gestational age.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, cord leptin levels were markedly higher in female than in male infants, and this difference was independent of birth weight and gestational age. Although the sexual dimorphism in leptin levels becomes most apparent at the onset of puberty, a significant gender difference in leptin levels at birth has previously been reported by some (9,(15)(16)(17)(18), but not all studies (12,20). It is discussed that these gender differences might reflect the transient perinatal elevation in sex steroids, as estrogens are associated with higher leptin concentrations, while androgens are inversely related to leptin levels (18).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To date, studies have produced mixed evidence regarding a sex diff erence in umbilical vein T. Some studies have found that compared with female newborns, male newborns have more umbilical vein T (Herruzo et al 1993), less (Pardo et al 2004), or virtually identical levels (van de Beek et al 2004). Establishing a norm for umbilical cord T is diffi cult because the commonly used ' direct ' assay methods (described below) lack the sensitivity to accurately detect T at levels below 10 nmol/l (Rosner et al 2007).…”
mentioning
confidence: 99%
“…Muito possivelmente, o mecanismo responsável por este dimorfismo não é um mecanismo que envolve hormônios sexuais (Pardo et al, 2004). As consequências fisiológicas e os mecanismos envolvidos na ontogenia sexoespecíficos das variáveis estudadas que apresentaram diferenças no presente estudo merecem mais observações.…”
Section: Volume Cardíacounclassified